Students’ Use and Perceptions of AI Grammar Checkers in English Grammar Learning - I Made Budana Yasa (English Education Department - Universitas Nasional Karangturi, 2025)
This study explores students’ use and perceptions of AI grammar checkers in English grammar learning. Conducted with 30 fourth-semester students of the English Language Education Study Program at Universitas Cokroaminoto Palopo, the research employed a descriptive quantitative design using a structured questionnaire consisting of 6 items related to usage and 12 Likert-scale items measuring perception. The questionnaire was adapted from previous studies and analyzed using SPSS version 26. The results indicate that the majority of students frequently used AI grammar tools, particularly Grammarly and QuillBot during academic writing, with most reporting that they discovered these tools through peers. Descriptive statistics showed high agreement on statements related to usefulness, such as helping identify mistakes (M = 1.40), improving writing quality (M = 1.97), and supporting learning from feedback (M = 2.00). However, concerns were also found regarding overreliance (M = 1.93), confusion with suggestions (M = 2.47), and trust in accuracy (M = 2.63). Interestingly, students did not prefer AI over human correction (M = 3.90), highlighting their continued reliance on teacher support. These findings suggest that AI grammar checkers are valuable supplementary tools when used critically and in combination with guided instruction.